2019
DOI: 10.3390/antibiotics8030123
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mycoplasma Activity of Daptomycin and Its Use for Mycoplasma Elimination in Cell Cultures of Rickettsiae

Abstract: Mycoplasma contamination detrimentally affects cellular functions and the growth of intracellular pathogens in cell cultures. Although several mycoplasmacidal agents are commercially available for sterile cell cultures, they are not applicable to rickettsia-infected cells. In our attempt to find an anti-mycoplasma drug for contaminated rickettsial cultures, we determined the susceptibilities of three common Mycoplasma species to daptomycin. Mycoplasma orale and M. arginini showed low-level resistance to daptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…However, the lipid II hypothesis was also rejected when it turned out that the addition of lipid II precursors did not antagonize daptomycin activity [84] and that it did neither bind to lipid II nor inhibited lipid II synthesis in vitro [85]. Further evidence against the lipid II hypothesis was provided by the observation that daptomycin is active against cell wall-less Mycoplasma orale and Mycoplasma arginini [86], cell wall-less B. subtilis L-forms [87], and non-growing S. aureus persister cells [88]. In contrast, daptomycin was inactive against E. coli protoplasts, suggesting that it is not the outer membrane barrier that renders it ineffective, but that the target of daptomycin is actually absent from Gram-negative bacteria.…”
Section: Is It Cell Wall Synthesis After All?mentioning
confidence: 99%
“…However, the lipid II hypothesis was also rejected when it turned out that the addition of lipid II precursors did not antagonize daptomycin activity [84] and that it did neither bind to lipid II nor inhibited lipid II synthesis in vitro [85]. Further evidence against the lipid II hypothesis was provided by the observation that daptomycin is active against cell wall-less Mycoplasma orale and Mycoplasma arginini [86], cell wall-less B. subtilis L-forms [87], and non-growing S. aureus persister cells [88]. In contrast, daptomycin was inactive against E. coli protoplasts, suggesting that it is not the outer membrane barrier that renders it ineffective, but that the target of daptomycin is actually absent from Gram-negative bacteria.…”
Section: Is It Cell Wall Synthesis After All?mentioning
confidence: 99%
“…In several studies, it has been discovered that DAP, in the presence of Ca 2+ ions, induces an increase in K + ions leakage which affects the difference in electrical potential across the membrane and the biosynthesis of basic molecules for the assembly of the cell wall, 28,40 even if it seems that DAP does not directly inhibit peptidoglycan synthesis. 41 Another possible scenario is linked to the DAP effect on the membrane curvature: in this case, the different geometries of some membrane regions could lead to a non-physiological distribution of specific membrane proteins, affecting their activity, 42 even if this mechanism of action has been questioned in other works. 43 Interestingly, several in vivo studies have shown that the membrane depolarization in bacteria is just partially present when DAP is used at a typical minimum inhibitory concentration (MIC), but it can occur completely at much higher concentrations and, at the same time, this phenomenon has a slow kinetics.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Considering the pivotal role of lipid II precursor in the enzymatic arrangement involved in peptidoglycan biosynthesis as well as in cell division, these findings offer an explanation about the cell wall synthesis inhibition observed in the presence of DAP; the mentioned interaction with lipid II precursor can induce the recruitment of fundamental protein complexes affecting physiological cellular processes. In several studies, it has been discovered that DAP, in the presence of Ca 2+ ions, induces an increase in K + ions leakage which affects the difference in electrical potential across the membrane and the biosynthesis of basic molecules for the assembly of the cell wall, , even if it seems that DAP does not directly inhibit peptidoglycan synthesis . Another possible scenario is linked to the DAP effect on the membrane curvature: in this case, the different geometries of some membrane regions could lead to a non-physiological distribution of specific membrane proteins, affecting their activity, even if this mechanism of action has been questioned in other works …”
Section: Introductionmentioning
confidence: 99%